Determinants of repeated abortion among women of reproductive age attending health facilities in Northern Ethiopia: a case-control study - Mussie Alemayehu; Henock Yebyo; Araya Abrha Medhanyie; Alemayehu Bayray; Misganaw Fantahun; Gelila Kidane Goba (BMC, 2017)
Abstract Background Every year, an estimated 19-20 million unsafe abortions take place, almost all in developing countries, leading to 68,000 deaths and millions more injured many permanently. Many women throughout the world, experience more than one abortion in their lifetimes. Repeat abortion is an indicator of the larger problem of unintended pregnancy. This study aimed to identify determinants of repeat abortion in Tigray Region, Ethiopia. Methods Unmatched case-control study was conducted in hospitals in Tigray Region, northern Ethiopia, from November 2014 to June 2015. The sample included 105 cases and 204 controls, recruited from among women seeking abortion care at public hospitals. Clients having two or more abortions ("repeat abortion") were taken as cases and those who had a total of one abortion were taken as controls ("single abortion"). Cases were selected consecutive based on proportional to size allocation while systematic sampling was employed for controls. Data were analyzed using SPSS version 20.0. Binary and multiple variable logistic regression analyses were calculated with 95% CI. Results Mean age of cases was 24 years (±6.85) and 22 years (±6.25) for controls. 79.0% of cases had their sexual debut in less than 18 years of age compared to 57% of controls. 42.2% of controls and 23.8% of cases cited rape as the reason for having an abortion. Study participants who did not understand their fertility cycle and when they were most likely to conceive after menstruation (adjusted odds ratio [AOR] = 2.0, 95% confidence interval [CI]: 1.1-3.7), having a previous abortion using medication (AOR = 3.3, CI: 1.83, 6.11), having multiple sexual partners in the preceding 12 months (AOR = 4.4, CI: 2.39,8.45), perceiving that the abortion procedure is not painful (AOR = 2.3, CI: 1.31,4.26), initiating sexual intercourse before the age of 18 years (AOR = 2.7, CI: 1.49, 5.23) and disclosure to a third-party about terminating the pregnancy (AOR = 2.1, CI: 1.2,3.83) were independent predictors of repeat abortion. Conclusion This study identified several factors correlated with women having repeat abortions. It may be helpful for the Government of Ethiopia to encourage women to delay sexual debut and decrease their number of sexual partners, including by promoting discussion within families about sexuality, to decrease the occurrence of repeated abortion.